Development of Grade 8 Human Nutrition Learning Outcomes through The 5 E’s of Inquiry-based Learning Combined with Board Games - Larpmahaprasert, Jirapat; Tantakanon , Kanjana; Thitajaroenwat, Nopphalak; Yamchuti , Hatthaya; Tang, Yae-Yu (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The purpose of this study is to: 1) create the 5E’s of Inquiry-Based Learning management system integrated with the board game "Magic Land of Nutrients" to achieve the 80/80 efficiency criterion; 2) assess improvements in learning outcomes on the "Nutrients in Humans" topic for Grade 8 students using the "Magic Land of Nutrients" board game and the 5E’s of inquiry-based learning approach; and 3) assess students' satisfaction with the integration of the two learning methods. The target group consists of twenty-three Suankularb Wittayalai Thonburi School Grade 8 students. Among the study tools are 1) learning management plans, 2) board games, 3) an assessment of learning achievement, and 4) a survey on student satisfaction. Data analysis involves identifying the relative gain score, mean, standard deviation, developmental testing of media and instructional packages (E1/E2). The research was grounded in the 5E model and game-based learning theory. Development score is calculated by the utilization of relative gain score to evaluate student improvement.The results show that: 1) the "Magic Land of Nutrients" board game and the 5E’s of inquiry-based learning management plan exceeded the 80/80 efficiency requirement with an efficiency of 84.06/80.22. 2) Students had an overall average relative gain score of 65.66 in academic achievement on the topic of Human Nutrition, indicating a high level of improvement. 3) Students expressed a high level of satisfaction (μ = 3.92, σ = 0.80).